Thematic approaches in Malaysian art since the 1990s - Abdullah, Sarena (2011)
This paper discusses on the impact of thematic approaches taken by Malay artists in Malaysia since the 1990’s.Malaysian art has become increasingly diverse in terms of its approach, subject, theme and media. This growing artistic diversity is discussed within a postmodern framework and is representative of a shift in tendencies away from a purely Malay/Islamic-centred artistic tradition to a more postmodern approach that is inclusive of Malaysia’s emerging middle class. Since the 1990’s, works produced by Malay artists have taken a more critical perspective aligned with the postmodern situation or situasi percamoden in accordance with Malaysia’s leapfrog into modernization. Through their works, Malay artists raise concerns and issues pertaining to the consequences of development and modernization, and explore themes ranging from social problems, environment and urbanization, and contemporary issues thereby employing postmodernist approaches in their art.